A People's Church : Medieval Italy and Christianity, 1050-1300 (Book collections on Project MUSE., 2023)
A People's Church brings together a distinguished international group of historians to provide a sweeping introduction to Christian religious life and institutions in medieval Italy. Each essay treats a single theme as broadly as possible, highlighting both the unique aspects of medieval Christianity on the Italian peninsula and the beliefs and practices it shared with other Christian societies. Because of its long tradition of communal self-governance, Christianity in medieval Italy, perhaps more than anywhere else, was truly a "people's church." At the same time, its exceptional urban wealth and literacy rates, along with its rich and varied intellectual and artistic culture, led to diverse forms of religious devotion and institutions.0Contributors: Maria Pia Alberzoni on heresy; Frances Andrews on urban religion; Cecile Caby on monasticism; Giovanna Casagrande on mendicants; George Dameron on Florence; Antonella Degl'Innocenti on saints; Marina Gazzini on lay confraternities; Maureen C. Miller on bishops; Agostino Paravicini Bagliani and Pietro Silanos on the papacy and Italian politics; Antonio Rigon on clerical confraternities; Neslihan Senocak on the pievi and care of souls; Giovanni Vitolo on Naples.